Consequences of Increasing Hypoxic Disturbance on Benthic Communities and Ecosystem Functioning - Villnäs, Anna (Public Library of Science, 2012)
Disturbance-mediated species loss has prompted research considering how ecosystem functions are changed when biota is impaired. However, there is still limited empirical evidence from natural environments evaluating the direct and indirect (i.e. via biota) effects of disturbance on ecosystem functioning. Oxygen deficiency is a widespread threat to coastal and estuarine communities. While the negative impacts of hypoxia on benthic communities are well known, few studies have assessed in situ how benthic communities subjected to different degrees of hypoxic stress alter their contribution to ecosystem functioning. We studied changes in sediment ecosystem function (i.e. oxygen and nutrient fluxes across the sediment water-interface) by artificially inducing hypoxia of different durations (0, 3, 7 and 48 days) in a subtidal sandy habitat. Benthic chamber incubations were used for measuring responses in sediment oxygen and nutrient fluxes. Changes in benthic species richness, structure and traits were quantified, while stress-induced behavioral changes were documented by observing bivalve reburial rates. The initial change in faunal behavior was followed by non-linear degradation in benthic parameters (abundance, biomass, bioturbation potential), gradually impairing the structural and functional composition of the benthic community. In terms of ecosystem function, the increasing duration of hypoxia altered sediment oxygen consumption and enhanced sediment effluxes of NH(4) (+) and dissolved Si. Although effluxes of PO(4) (3−) were not altered significantly, changes were observed in sediment PO(4) (3−) sorption capability. The duration of hypoxia (i.e. number of days of stress) explained a minor part of the changes in ecosystem function. Instead, the benthic community and disturbance-driven changes within the benthos explained a larger proportion of the variability in sediment oxygen- and nutrient fluxes. Our results emphasize that the level of stress to the benthic habitat matters, and that the link between biodiversity and ecosystem function is likely to be affected by a range of factors in complex, natural environments.